Simultaneous production of triacylglycerol and high-value carotenoids by the astaxanthin-producing oleaginous green microalga Chlorella zofingiensis. (August 2016) - Liu, Jin; Mao, Xuemei; Zhou, Wenguang; Guarnieri, Michael T.
Highlights: Stress conditions induced TAG and astaxanthin production in C. zofingiensis. A strong correlation between TAG and astaxanthin accumulation was observed. Simultaneous TAG and astaxanthin production in semicontinuous modes was optimized. High TAG and astaxanthin productivities (297 and 3.3 mg L −1  day −1 ) were obtained. Inhibiting de novo fatty acid biosynthesis enhanced astaxanthin accumulation. Abstract: The production of lipids and astaxanthin, a high-value carotenoid, by Chlorella zofingiensis was investigated under different culture conditions. Comparative analysis revealed a good correlation between triacylglycerol (TAG) and astaxanthin accumulation in C. zofingiensis . Stress conditions promoted cell size and weight and induced the accumulation of neutral lipids, especially TAG and astaxanthin, with a concomitant decrease in membrane lipids. The highest contents of TAG and astaxanthin achieved were 387 and 4.89 mg g −1 dry weight, respectively. A semi-continuous culture strategy was developed to optimize the TAG and astaxanthin productivities, which reached 297 and 3.3 mg L −1  day −1, respectively. Additionally, astaxanthin accumulation was enhanced by inhibiting de novo fatty acid biosynthesis. In summary, our study represents a pioneering work of utilizing Chlorella for the integrated production of lipids and high-value products and C. zofingiensis has great potential to be a promising production strain and serve as an emerging oleaginous model alga.